Influence of Organizational Culture on Performance of the Automotive Engineering Industry in Nairobi City County in Kenya - Njuguna, Roselyn; Kihara, Allan (American Journal of Strategic Studies, 2024)
Purpose: The general objective of the study was to investigate influence of organizational culture on performance of the automotive engineering industry in Nairobi City County in Kenya. The study specifically sought to determine the influence of organizational structure, level of collectivism and organizational learning on performance of the automotive engineering industry in Nairobi City County in Kenya. Methodology: The study adopted the use of descriptive research design and targeted a population is 341 respondents from the automotive industry. Stratified random sampling was used selecting the respondents from automotive organizations. The sample size consists of 184 respondents. The study used structured questionnaires to obtain primary data for analysis. Once the data was collected, the cleaned data was entered into the Statistical Package for the Social Sciences (SPSS) software. SPSS, specifically version 28, was utilized for both descriptive and inferential statistical analyses. Findings: The study established that organizational structure, level of collectivism and organizational learning positively and significantly influences performance of the automotive engineering industry in Nairobi City County in Kenya.The study concludes that organizational structure significantly impacts performance within the automotive industry. Secondly, a collectivist culture, characterized by shared values, team cohesion, and mutual support, significantly enhances organizational effectiveness. Organizational learning's impact on performance within the automotive industry reveals that structured employee training, knowledge sharing, and cross-functional collaboration are pivotal in driving organizational success. Unique contribution to theory, practices and policy: Automotive companies should evaluate their organizational structures and consider a balanced approach that combines elements from hierarchical, network, and flat structures. Centralized decision-making might be retained for strategic decisions, but operational processes could benefit from a network or flat structure to enhance agility and innovation. Organizations should cultivate a collectivist culture to strengthen team cohesion and collaboration. This involves promoting shared goals, mutual support, and continuous improvement. Companies should leverage digital collaboration tools to maintain team cohesion in remote or hybrid work settings and encourage a culture where ideas and feedback are freely exchanged. Automotive companies should actively cultivate and reinforce collectivist values, such as teamwork, mutual support, and shared goals. This can be achieved through regular team-building activities, fostering a culture of open communication, and creating opportunities for collaborative problem-solving. To further refine and build on the recommendations for improving performance in the automotive industry, several avenues for research could be pursued.